A rare case of 46, XX gonadal dysgenesis, Mayer–Rokitansky–Kuster–Hauser syndrome, pituitary and thyroid hypoplasia. (10th February 2022) - Ambachew, Rediet; Gulilat, Amare; Aberra, Tewodros; Terefework, Zewdu; Bedilu, Wubalem; Tarekegn, Getahun; Reja, Ahmed
Abstract : Summary: Mayer–Rokitansky–Kuster–Hauser syndrome is characterized by congenital absence or hypoplasia of the uterus and upper two-thirds of the vagina in both phenotypically and karyotypically normal females with functional ovaries, whereas gonadal dysgenesis is a primary ovarian defect in otherwise normal 46, XX females. An association between these two conditions is extremely rare. We report a 21-year-old female presented with primary amenorrhea and undeveloped secondary sexual characteristics. The karyotype was 46, XX and the hormonal profile revealed hypothyroidism and hypogonadotropic hypogonadism. Pelvic MRI showed class I Mullerian duct anomaly with ovarian dysgenesis. Ultrasound showed bilateral thyroid hypoplasia and brain MRI suggested anterior pituitary hypoplasia. Levothyroxine and hormone replacement therapy were started. Learning points: The simultaneous presentation of 46, XX gonadal dysgenesis, Mayer–Rokitansky–Kuster–Hauser syndrome, hypothyroidism, and pituitary hypoplasia is a Possibility. Extensive evaluation should be made when a patient presents with one or more of these features. The diagnosis imposes a significant psychological burden on patients and adequate counseling should be provided. Hormone replacement therapy remains the only therapeutic option for the development of secondary sexual characteristics and the prevention of osteoporosis.